DIAVA (Psidium Guajava) ANTI KETOMBE - Sutanti Sutanti; Fadzillah Azzahra; Salsabila Ignacia Algren; Sindi Oktavia (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
Guava leaves or the scientific name Psidium Guajava Lare plants found throughout Indonesia, a country with a tropical climate. The leaves have pinnate bones and the color of the leaves on the upper side looks smoother green compared to the lower side, which has a wrinkled leaf surface. This research is aimed at creating new innovative shampoo products using natural ingredients in the form of guava leaves. The goal is that guava leaf plants are not only used as organic waste but can be utilized effectively by finding new innovations. This research was conducted at SMA Negeri 1 Manyaran. In this research, the materials used were Psidium Guajava L guava leaves, lerak, lime, coconut oil, texapon, distilled water. With 2 treatments, namely the ratio of guava leaves and distilled water, A1 = 100 gr : 100 ml, A2 = 150 gr : 100 ml. From the organoleptic test that we carried out with 15 respondents with the ratio A1 = 100 gr: 100 ml, this was the best result, including color, aroma and texture tests. Meanwhile, laboratory tests at the Integrated Research and Testing Laboratory (LPPT) at Gajah Mada University, Yogyakarta, showed that the saponification number was 18.34 cm. So the foam in Diava is able to keep the shampoo in the hair, makes hair easy to wash, and prevents hair strands from coming together, causing tangles.